Feminicides and public policies: declarations of gender Violence alerts in mexico, 2015-2017 (2018)
In this paper we follow the process of requesting the gender violence alert against women in Mexico, to identify spatially and temporally the acceptance and / or denial by the State and the implementation of public policies where there is a higher prevalence of violence. We start from a feminist geography that considers that space is transformed with social actions, for that reason we identify feminist groups that demand changes in the lives of women. We use the descriptive methodology to know the processes, people and demands of civil society, the prevailing situations and attitudes to identify the relationships that exist between two or more variables: the political activity of civil subjects, ways of acting, motivations and opposition of the State. Among the main results found, it stands out that the average that took the processes of the gender violence alert was 2 years 2 months; the percentage of federative entities where the declarations have been accepted is 37.5 % a, that of not approved is 21.8 %, in process of 21.8 % and 18.7 % in those that have not been requested, at the moment of the writing of this article. The information contributes to the knowledge of the facts and to identify how difficult it is that the femicide violence is assumed as a public problem.